Banking on Satisfaction: A Study of Job Satisfaction among Employees in Malaysian Banks - Wong Loke Suan Chris Daniel; Assoc. Prof. Dr. Mahaganapathy Dass; Dr. Farzana Nazera; Kazi Tanvir (HM Journals, 2024)
The present study aims to examine the many elements that exert an influence on job satisfaction among employees within the banking sector in Malaysia. This study investigates three hypotheses: (1) There exists a negative correlation between work-life balance and job satisfaction; (2) Effective leadership and management have a positive influence on job satisfaction; and (3) Competitive compensation and benefits have a beneficial effect on job satisfaction. The results of the study provide empirical evidence for each of the three hypotheses. The findings indicate that Malaysian banks have the potential to improve employee job satisfaction through the implementation of strategies that prioritize work-life balance, effective leadership and management, and competitive remuneration and benefits packages. These initiatives are expected to enhance personnel engagement and productivity, hence fostering organizational success within the highly competitive Malaysian banking sector.